Object-oriented model of the seismic vulnerability of the fuel distribution network in coastal British Columbia. (June 2019) - Costa, Rodrigo; Haukaas, Terje; Chang, Stephanie E.; Dowlatabadi, Hadi
Highlights: Just-in-time fuel inventories reduce resilience against fuel shortages. Subduction earthquakes can cause widespread fuel shortages. Localized fuel shortages after earthquakes are likely in the next 50 years. A new object-oriented network model was developed to explore resilience scenarios. Local emergency planners helped improve simulations and build realistic solutions. Abstract: An agent-based object-oriented model for the fuel distribution network in coastal British Columbia in Canada is presented. Objects representing infrastructure components with varied attributes and behaviors are described together with objects representing transportation modes on land and on water. A novel feature of the modeling approach is its capacity to represent the diverse nature of the objects in a network. Another novelty of the approach is its capacity to simulate discrete deliveries based on requests, which is a requirement in the modeling of the considered fuel distribution network. This paper presents the software architecture and applies it to assess the probability of fuel shortages following an earthquake for six storage facilities in coastal British Columbia. The results of this assessment can be used to inform emergency response plans.